2006
DOI: 10.1002/sca.4950280506
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA and RNA from retroviruses using ribonuclease A

Abstract: Summary: Retroviruses, such as human immunodeficiency virus (HIV), can be disrupted with chemical agents and made to disgorge their encapsidated nucleic acid. The products can be visualized by atomic force microscopy (AFM). Retroviruses may contain both viral genomic RNA and reverse transcribed DNA produced prior to integration into the host cell genome. It is necessary to know which molecules are RNA and which are DNA in order to interpret the events that transpire during infection. DNA, when imaged by AFM, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…A method was devised for additional identification based on exposure of the nucleic acid to high concentrations of bovine RNase A (27). One example of results from that study is shown in Fig.…”
Section: Visualization Of Viral Rna and Dnamentioning
confidence: 99%
“…A method was devised for additional identification based on exposure of the nucleic acid to high concentrations of bovine RNase A (27). One example of results from that study is shown in Fig.…”
Section: Visualization Of Viral Rna and Dnamentioning
confidence: 99%
“…Sometimes, however, the distinction is not entirely clear and further evidence may be needed to show whether a filament, strand, or complex is DNA or RNA. A method was devised for additional identification based on exposure of the nucleic acid to high concentrations of bovine RNase A (42). RNA, naturally, was hydrolyzed to small pieces by RNase A and left only fragments on the substrate which corresponded to protected stem-loops.…”
Section: Imaging Of Nucleic Acids Of Virusesmentioning
confidence: 99%
“…AFM analysis was carried out using a Nanoscope III multimode instrument (Veeco Instruments, Santa Barbara, CA). Imaging procedures were fundamentally the same as described for previous investigations of viruses (Kuznetsov et al, 2001(Kuznetsov et al, , 2002(Kuznetsov et al, , 2003; and RNA (Kuznetsov et al, 2005b;Kuznetsov and McPherson, 2006). For scanning in air, silicon tips were employed.…”
Section: Methodsmentioning
confidence: 99%